Analisa Dampak Kebijakan Pemerintah Terhadap Kinerja Keuangan Bank Umum Syariah di Indonesia Pada Era Pandemi Corona Virus Disease-19 - Fatkhur Rohman Albanjari; Rina Prihatin; Suprianto Suprianto (Universitas Muhammadiyah Ponorogo, 2021)
The purpose of this study is to analyze the impact of government policies on financial performance at Islamic Commercial Banks in Indonesia during the period January to September 2020. The sample used in this study is Islamic Commercial Banks that have been registered in Indonesia with a research population of a number of 5 Sharia Bank. The author uses descriptive quantitative research methods with the variable Financing Deposit Ratio (FDR), Non-Performing Financing (NPF) during the COVID-19 pandemic. The results showed that the financing deposit ratio in Islamic commercial banks in the first and second quarters had an average increase, meaning that financial health declined along with government policy from implementing PSBB to New Normal. Meanwhile, in the third quarter it has experienced a decrease of close to 75% so that it can be concluded that financial health is more stable. The results show that non-performing financing at Islamic commercial banks tends to be more stable, so it can be said that Islamic Commercial Banks in the COVID-19 pandemic era tend to be healthy.